DFT and MD simulation supplemented experiments for isotopic fractionation of zinc compounds using a macrocyclic crown ether appended polymeric resin. Issue 26 (23rd June 2020) - Singha Deb, A. K.; Sahu, P.; Boda, A.; Ali, Sk. M.; Shenoy, K. T.; Upadhyay, D.
Abstract : Isotope effect is a quantum mechanical phenomenon and thus poses a challenge for the separation of isotopes of an element of interest, especially for heavy elements. Abstract : Isotope effect is a quantum mechanical phenomenon and thus poses a challenge for the separation of isotopes of an element of interest, especially for heavy elements. Isotopic fractionation of zinc is also quite difficult and challenging but is necessitated due to various applications of its isotopes ranging from nuclear medicine to nuclear power reactors. Here, we developed the dibenzo-18-crown-6 (DB18C6) ether-functionalized poly(methacrylic acid) (PMA) resin by exploiting the ion and isotope recognition ability of the crown ether using DFT/MD simulations followed by experiments for isotopic fractionation of zinc. The PMADB18C6 adsorbent was prepared and suitably characterized. Both computational and experimental findings demonstrate that the adsorption and isotope separation of zinc with PMADB18C6 are due to the molecular recognition effect of the "O" dipole of the crown ether. Furthermore, both MD simulations and experiments suggest Langmuir type adsorption isotherms. The adsorption of Zn 2+ ions on the PMA resin is predicted to be endothermic, whereas it is exothermic on the PMADB18C6 resin, as revealed from the experimentally observed enthalpy change. A small scale fixed bed column study was demonstrated to test the scale-up application. The values of the experimental separation factors: 1.0013 for 66/64 and 1.0027 for 68/64 confirm the computationally predicted results of 1.00088 and 1.0010, respectively, thus establishing the combined strength of the theory and experiments for the identification of efficient fractionating agents for a complex quantum isotope effect which eventually helps in planning further experiments in view of medicinal and technological applications of zinc isotopes.